IS THIS THE END OF QUOTATION? NOTES ABOUT “LITERARY QUOTATION” CULTURE - H. F. Ovcharenko (Концепт: философия, религия, культура, 2018)
This article analyses the classic quotation destiny in modern literary texts through culture and ethics collision. Unfortunately, on the one hand, “Antiplagiat” does not suit for that case and on the other hand, quotation definition as “a group of words taken from a text or speech and re- peated by someone other than the original author or speaker” with indispensable reference “is dead”. Postmodernism gives the preference to plagiarism (“literary stealing”), to compilation, to cento. Hypertext, the term from Internet, signifies different transformations of literary texts, including “a new work” made from fragments of published books/blogs etc. Of course, this is not a modern idea. Far back in the past, some antique authors utilized plagiarism and cento as a literary method (!). Today researchers often speak about intertextuality. Can it really be true, that we observe the end of classic quotation? Undoubtedly, the problem of “polyquotation” without references inevitably leads to the ethical questions of authorship, literary property.Antiplagiarism check for the dissertations written by public figures or ministers is attractive to everyone; meanwhile the situation with quotations in literary texts is completely different. Therefore, we would like to draw attention to quotation, illustrating the analysis with concrete examples. It is up to the reader to decide if this is the end of quotation.